(18)F-FDG silicon photomultiplier PET/CT: A pilot study comparing semi-quantitative measurements with standard PET/CT - Baratto, Lucia (PLoS One, 2017)
PURPOSE: To evaluate if the new Discovery Molecular Insights (DMI) PET/CT scanner provides equivalent results compared to the standard of care PET/CT scanners (GE Discovery 600 or GE Discovery 690) used in our clinic and to explore any possible differences in semi-quantitative measurements. METHODS: The local Institutional Review Board approved the protocol and written informed consent was obtained from each patient. Between September and November 2016, 50 patients underwent a single (18)F-FDG injection and two scans: the clinical standard PET/CT followed immediately by the DMI PET/CT scan. We measured SUV(max) and SUV(mean) of different background organs and up to four lesions per patient from data acquired using both scanners. RESULTS: DMI PET/CT identified all the 107 lesions detected by standard PET/CT scanners, as well as additional 37 areas of focal increased (18)F-FDG uptake. The SUV(max) values for all 107 lesions ranged 1.2 to 14.6 (mean ± SD: 2.8 ± 2.8), higher on DMI PET/CT compared with standard of care PET/CT. The mean lesion:aortic arch SUV(max) ratio and mean lesion:liver SUV(max) ratio were 0.2–15.2 (mean ± SD: 3.2 ± 2.6) and 0.2–8.5 (mean ± SD: 1.9 ± 1.4) respectively, higher on DMI PET/CT than standard PET/CT. These differences were statistically significant (P value < 0.0001) and not correlated to the delay in acquisition of DMI PET data (P < 0.0001). CONCLUSIONS: Our study shows high performance of the new DMI PET/CT scanner. This may have a significant role in diagnosing and staging disease, as well as for assessing and monitoring responses to therapies.